(untitled) (Journal of Science and Technology, 2016)
This paper proposes a new algorithm for boosting in kernel density estimation (KDE). This algorithm enjoys the property of a bias reduction technique like other existing boosting algorithms and also enjoys the property of less function evaluations when compared with other boosting schemes. Numerical examples are used and compared with existing algorithm and the findings are comparatively interesting.